The Role of Digital Learning Media in Developing Critical Thinking Skills of Elementary School Students - Nabila Nur Khasanah; Nawal Isya Khairani; Suparmi (Al-Ard: Journal of Education, 2025)
The development of digital technology has brought significant changes in the field of education, particularly in how teachers and students interact during the learning process. One of the positive impacts of digital technology advancement is the increasing use of digital learning media to enhance critical thinking skills among elementary school students. Critical thinking is one of the essential 21st-century skills that must be taught from an early age to enable students to analyz, evaluate, and solve problems independently. This study employs a library research method (literature review) with a qualitative approach, reviewing various scientific journals published between 2020 and 2025 through google scholar and Publish or Perish that discuss the relationship between digital media and critical thinking skills. The analysis results indicate that digital learning media such as interactive PowerPoint, instructional videos, online quizzes, Android-based educational games, and flipbooks can enhance student engagement, facilitate concept comprehension, and develop critical thinking skills. Therefore, digital learning media play an important role as effective tools to create more interactive and engaging learning experiences while supporting the optimal development of elementary students’ critical thinking skills.